1985
DOI: 10.1007/bf01806058
|View full text |Cite
|
Sign up to set email alerts
|

Possible control of gibberellin-induced release of temperature-dependent primary dormancy in seeds of celery (Apium graveolens L.) by transmembrane ion fluxes

Abstract: Abstract. The temperature-dependent primary dormancy of cv Florida 683 celery seeds in darkness was broken by GA,, (2 X lo-' M) alone but other growth regulators such as BA, ethephon or daminozide were necessary to break dormancy of cv Lathom Blanching seeds in the presence of GA,, at this concentration. Although AgNO, partially inhibited both the ethephon-and BA-induced germination of cv Lathom Blanching seeds in the presence of GA.,,, in the dark it did not affect the promotive action of daminozidc. Ethephon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…moist-chilled seeds compared with the other tested treatments had higher germination percentage and reducing T 50 . The effect of cold treatment on seed dormancy breaking has also been confirmed in our previous research [12][13][14][15] and for other plants of Apiaceae such as: Osmorhiza [7,8], Ptilianium nuttalli [9] Anthriscus sylvestris [24], Perideridia gairdner i [10], Apium graveolens [11]. Moreover, this treatment produced seedlings of better growth characteristics than control seeds ( Table 2).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…moist-chilled seeds compared with the other tested treatments had higher germination percentage and reducing T 50 . The effect of cold treatment on seed dormancy breaking has also been confirmed in our previous research [12][13][14][15] and for other plants of Apiaceae such as: Osmorhiza [7,8], Ptilianium nuttalli [9] Anthriscus sylvestris [24], Perideridia gairdner i [10], Apium graveolens [11]. Moreover, this treatment produced seedlings of better growth characteristics than control seeds ( Table 2).…”
Section: Discussionsupporting
confidence: 78%
“…Various dormancy breaking and germination stimulating treatments have been tried with seeds of many species of Apiaceae such as Osmorhiza [7,8] Ptilianium nuttalli [9] Perideridia gairdneri [10], Apium graveolens [11] and Ferula ovina [12][13][14][15][16]. In this respect, gibberellic acid and moist-chilling treatments seem the most promising in many species of Apiaceae (ISTA) such as Ferula ovina [14].…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence to suggest that gibberellin-involvement in celery seed germination may be controlled through the effect of these hormones on transmembrane ion fluxes [5] . Such a mechanism could regulate the availability of gibberellin to bind with proteins and could form the basis for light and temperature effects on celery seed germination .…”
Section: Discussionmentioning
confidence: 99%
“…Florida 683, a cultivar with shallow dormancy, germination can be stimulated in the dark at high temperature by addition of the gibberellins A4 and A, (GA4, 7) to the incubation solution . In more dormant cultivars, other plant growth substances, particularly those with cytokinin Abbreviations ; AC94,377, 1-(3-chlorophthalimido)-cyclohexane carboxamide ; ancymidol, a-cyclopropyl-a-(4-methoxyphenyl)-5-pyrimidinemethanol ; AMO1618, N,N,N-2-tetramethyl-5-(l-methyl ethyl)-4-(l-piperidinylcarbonyl)oxy-benzenaminium chloride; BTS44584, S-2,5-dimethyl-4-pentamethylenecarbamoyloxyphenyl-SS-dimethyl sulphonium P-toluenesulphonate ; chlormequat chloride, 2-chloroethyltrimethylammonium chloride ; daminozide, N-dimethylaminosuccinamic acid ; paclobutrazol, (2RS, 3RS)-l-(4-chlorophenyl)-4,4-dimethyl-2-(lH-1,2,4-triazol-l-yl pentan- 3-ol . activity are required in addition to the GA 417 [5,9] . Previously, it was demonstrated that endogenous cytokinins may be involved in the mechanism controlling light-stimulated dormancy break in celery, and that this involved interconversion of cytokinins rather than de novo biosynthesis [6] .…”
Section: Introductionmentioning
confidence: 99%